Does diet variation determine the digestive tract length of Capoeta banarescui Turan, Kottelat, Ekmekci and Imamoglu, 2006?. (4th June 2016) - Akin, S.; Turan, H.; Kaymak, N.
Summary: This study tested the spatial variations in the digestive/intestine tract length of Capoeta banarescui, with regard to their diets in different habitats. Highly varied diets observed in a previous study within the same river system posed the question whether this flexibility is reflected in the digestive tract and intestine length of the species in the Yeşilırmak River, Turkey. Totals of 382 specimens (standard length 4.6–19.1 cm) were captured by electro‐fishing along the river in September 2012 at 11 locations spanning elevations from 34 to 992 m. The stomach, intestine and total digestive tract lengths were measured, and stomach contents analysed from 196 specimens. For statistical analyses, the stomach, intestine and total digestive tract length were expressed as percentages of total weight and standard length. The data provided evidence that the digestive tract and intestine lengths varied significantly among locations in association with the diet. Fish having dominantly carnivorous diets (e.g. chironomid larvae/invertebrates) in two locations had significantly shorter intestines and digestive tracts than those with diets dominated by benthic algae and other plants. The data indicated that C. banarescui showed broad flexibility in their feeding habits. Feeding heavily on plant materials might lead to the development of longer digestive tracts, increasing the active surface area for digestion; alternatively, there may be less invested in development of the digestive tract when feeding primarily on carnivorous diets where the respective digestive enzymes are readily available. The data suggest that phenotypic plasticity in the digestive tract length of C. banarescui is associated more with the abundant protein‐rich carnivorous food sources in the studied habitats. Whether this digestive tract plasticity has a genetic background remains to be verified in future studies.